PERSPEKTIF PIDANA TERHADAP PERISTIWA BENCANA PERTAMBANGAN - Reine Rofiana (Universitas 17 Agustus 1945 Samarinda, 2018)
The perceived impact of coal mining is a condition of nature damaged plus conflict (because claimed lives). In the span of four years (2011-2015) has more than 10 innocent children become victims which there is no clarity of the settlement of legal cases until now.This paper is more focused on normative writing that is by reviewing some references related to the coal mining is connected by legal theories and regulations. According to the author's perspective, based on the theory that is stated by Emile Duekheim and Robert K. Merton, mining case has been deviated due to the weak awareness of the Mining Company by complying of prevailing laws and regulations.The authors suggest that by upholding of true criminal objective it should be expected that all existing Mining Companies should have fear so as to prevent similar caseswill happen in the future and for be more sensitive and responsible in managing his company. And from Respressive Function it is necessary in order to educate the Mining Company so as to have a high legal awareness.